Oral versus written feedback delivery to nursing students in clinical education: A randomized controlled trial - Vida Tayebi; Mohammad Reza Armat; Hamid Tavakoli Ghouchani; Fatemeh Khorashadizadeh; Alireza Gharib (Electronic Physician, 2017)
Background: Feedback delivery is deemed as a key element during a students' clinical education. It keeps students on track to meet their goal and increase students' motivation and confidence. Objective: The aim of this study was to compare the quality of feedback delivery in oral versus written feedback delivery to nursing students in clinical education. Methods: A randomized controlled trial was conducted between February and August 2012 in the city of Bojnurd in Iran. Using purposive sampling, last semester’s nursing students (n=44) had been randomly assigned to oral and written feedback delivery groups. Three Instructors received orientation and training on methods of feedback delivery before study initiation. Then, they gave necessary oral and written feedback to the students. Clinical settings of the study included coronary care, surgical, and neonatal units of hospitals. Data collection tools were quality of feedback delivery, students' satisfaction questionnaire and students' reactions checklist. Data were analyzed using SPSS version 11.5 with chi-square test and the t-test. Results: Most of the students (52%, n=23) were male. There were no significant differences between the scores of quality of oral and written feedback delivery (p>0.05). The study did not show a difference of satisfaction level between the oral and written feedback groups. The relationship between students' reactions and feedback type at the confidence level of 90% was significant, so that students who received oral feedback showed more severe reactions as compared to the written feedback group. Conclusion: According to the results, the type of feedback is not an important factor in clinical education quality and satisfaction level. They may achieve a better outcome by focusing on the other aspects of quality of feedback delivery rather than feedback type. Trial registration: The trial was registered at the Iranian Registration Center for Clinical Trials with the Irct id: (IRCT: 201111128076N1). Funding: North Khorasan University of Medical Sciences (permission no. 89/p/209).